Effects of a Velogenic Newcastle Disease Virus on Packed Cell Volume, Total Protein and Hemagglutination Inhibition Antibody Titres of Vaccinated Shikabrown Cocks - Rwuaan, J.S.; Rekwot, P.I.; Abdu, P.A.; Eduvie, L.O.; Obidi, J.A. (International Journal of Poultry Science, 2009)
Fifty 20 week old Shikabrown cocks consisting of 22 red Shikabrown and 28 white Shikabrown cocks were purchased from the National Animal Production Research Institute, Shika and used for this study. Twenty-five of the cocks made up of 12 red and 13 white cocks selected on basis of weight were infected with 2 ml of 106.0 EID5.0 of a Velogenic Kudu 113 strain of Newcastle disease virus intranasally and orally. The remaining twenty-five cocks made up of 14 red and 11 white served as control. Blood samples were taken from the wing veins of both infected and control cocks and centrifuged in a Hermle Z364 centrifuge at 251.6 g for packed cell volume, total protein and Newcastle disease antibody titres. There was no significant difference in the packed cell volume of the control and infected red Shikabrown cocks. Similarly there was no significant difference in the packed cell volume of the control and infected white Shikabrown cocks, although the infected cocks had slightly lower values. Total protein did not show any significant difference between the control and infected red cocks and between the control and infected white cocks. The antibody titres of the control red and white cocks were significantly (p